Phoneprioception: Enabling Mobile Phones to Infer Where they Are Kept - Wiese, Jason; Saponas, Scott; Brush, A.J. (CHI 2013, 2013)
Enabling phones to infer whether they are currently in a pocket, purse or on a table facilitates a range of new interactions from placement-dependent notifications setting to preventing “pocket dialing.” We collected data from 693 participants to understand where people keep their phone in different contexts and why. Using this data, we identified three placement personas: Single Place Pat, Consistent Casey, and All-over Alex. Based on these results, we collected two weeks of labeled accelerometer data in-situ from 32 participants. We used this data to build models for inferring phone placement, achieving an accuracy of approximately 85% for inferring whether the phone is in an enclosed location and for inferring if the phone is on the user. Finally, we prototyped a capacitive grid and a multispectral sensor and collected data from 15 participants in a laboratory to understand the added value of these sensors.